2007
DOI: 10.1038/sj.ijo.0803692
|View full text |Cite
|
Sign up to set email alerts
|

Associations between long-term physical activity, waist circumference and weight gain: a 30-year longitudinal twin study

Abstract: Background and objective: Physical activity level and obesity are both partly determined by genes and childhood environment. To determine the associations between long-term leisure-time physical activity, weight gain and waist circumference and whether these are independent of genes and childhood effects. Design and subjects: The study design is a 30-year follow-up twin study in Finland. For this study, 146 twin pairs were comprehensively identified from the large Finnish Twin Cohort. These twin pairs were dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
150
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(165 citation statements)
references
References 47 publications
11
150
0
4
Order By: Relevance
“…Interestingly, the distribution of fat storage in the selected mice occurred more in the visceral compartment than in control mice. This unexpected result seems counterintuitive at first, given that the increased physical activity is generally negatively associated with risk factors for the development of the metabolic syndrome in humans 26,27 and rodents. 28 However, because the visceral depot might overlap with the center of gravity of four-legged animals, we can speculate that fat storage in this area, rather than other areas, may be relatively advantageous to facilitate sustained endurance running behavior.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, the distribution of fat storage in the selected mice occurred more in the visceral compartment than in control mice. This unexpected result seems counterintuitive at first, given that the increased physical activity is generally negatively associated with risk factors for the development of the metabolic syndrome in humans 26,27 and rodents. 28 However, because the visceral depot might overlap with the center of gravity of four-legged animals, we can speculate that fat storage in this area, rather than other areas, may be relatively advantageous to facilitate sustained endurance running behavior.…”
Section: Discussionmentioning
confidence: 94%
“…There are very few studies, which take into account this kind of complex genetic confounding. However, a recent Finnish twin study with a 30-year follow-up of twin pairs discordant for physical activity showed that the sedentary twin gained 5.4 kg more weight and had 8.4 cm larger WC compared with their more active co-twin 10 indicating that independent of familial background, physical activity protects from weight gain, especially of that in the abdominal region. In this study, both genetic and environmental factors explained the cross-sectional associations between physical activity and WC as well as physical activity and BMI in females, among which additive genetic correlations were slightly stronger than specific environmental correlations.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Sedentary lifestyle is a strong predictor of obesity, 6 and physical activity is considered important in the prevention of weight gain. [7][8][9] Further, we have recently shown that persistent physical activity is associated with decreased rate of weight gain and a smaller waist circumference (WC) during a follow-up period of 30 years, 10 even after controlling for genetic background and shared environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…This suggested an indirect, timedependent effect of these parameters on force production, which might be mediated by an alteration of Ca 2+ fluxes throughout the sarcoplasmic reticulum (SR) [39]. In fact, it has been shown, that the decline in Ca 2+ release from SR occurs later in muscle fibers with high capacity for oxidative metabolism [40,41]. Thus, HCRs may have more efficient hydrogen ion buffering and delayed decline in Ca 2+ release due to higher oxidative capacity in skeletal muscle [19,32], which might help resist fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Leisure physical activity habits were assessed with identical validated questions on surveys conducted in 1975 and 1981 39,40 and with modified questions on the survey conducted in 1990 41 . Assessments of vigorous physical activity were based on a single set of intensity categories applied at all three time points; these were: 1) walking, 2) alternately walking and jogging, 3) jogging (light running), and 4) running.…”
Section: Assessment Of Predictors and Potentially Confounding Variablesmentioning
confidence: 99%